Adaptation of Tahfidz Students in the Digital Era: A Review from the Perspective of Islamic Education Paradigm at Islamic Boarding School of Qur’an Mihrob Maryam - Nurul Sakdiyah; Junaris, Imam (Journal of Development Research, 2025)
Technological development is advancing at a very rapid pace. This progress affects various aspects of life, including the field of Islamic education. Islamic Boarding School Islamic Boarding School Mihrob Maryam Garum is an institution based on Qur’an memorization (tahfidz), which enforces very strict rules prohibiting the use of gadgets to maintain the retention of Qur’anic memorization. However, a serious challenge arises when students complete their education and return to a society that is fully digitalized. They are faced with the need to adapt to technology while preserving the values of the Islamic Boarding School amid the overwhelming flow of information. This study aims to describe the forms of adaptation of tahfidz students to the digital era through the lens of the Islamic education paradigm. The research uses a descriptive qualitative approach, with data obtained through observations and interviews with the students and caretakers of the Islamic Boarding School. The findings show that tahfidz students are able to adapt selectively to the digital world by applying the values instilled during their time in the Islamic Boarding School, such as discipline, responsibility, and sincerity. The Islamic education paradigm serves as the foundation for shaping the students’ character so that they can utilize technology as a means of da’wah (religious propagation) and reinforcement of memorization, rather than merely for entertainment.